Impact of Gender inclusion in local government: A study based on Laltipur and Jhapa District (Patan Pragya, 2020)
This article focuses on the impact of gender inclusion in local government. This topic is based on gender inclusion theory, policy and programme of Nepalese government. This research examines the situation of knowledge of equal participation of female in decision making process, on policy and practices of local Government, and next is to understand the historical and patriarchal control over participation in decision making and influence of policy. It introduces to the Gender-aware approaches concerned with the manner in which such relationships are socially constructed; men and women play different roles in society, their gender differences being shaped by ideological, historical, religious, ethnic, economic and cultural determinants. It focuses on power relations and roles that challenges the existing women's subordination in the society. This research used in cross sectional descriptive and analytical research and all information is gathered and assessed on the issues- what and how they utilize resources benefits from local where the local people participate in different ways; what and how women use women's sectors fund and resources; how the social and cultural division of labour affecting in the decision making process in local government council and general meeting. Almost 90%respondents of study areas of both districts (Lalitpur and Jhapa) are affiliated political parties before they elected in local government. Almost 50 % people of both Jhapa and Lalitpur district have the knowledge of gender inclusion. The practice of implementation of the formulated policies - program is gradually increasing in local government but still takes time to implement completely, but it seems that there is lacking of an effective awareness campaign. Increasing local government authority over service provision is pursued in part to reduce the gap between citizens and government authorities, as local government is considered closer to constituents. Whether or not LGs are able to continue to provide and improve services and develop infrastructure will be critical to the success of the new governance structure.